2023
DOI: 10.3390/bs13030215
|View full text |Cite
|
Sign up to set email alerts
|

Heart Rate as a Correlate for the Emotional Processing of Body Stimuli in Anorexia Nervosa

Abstract: In anorexia nervosa, aberrant emotional reactions toward body stimuli have been discussed. We investigated heart rate as a physiological marker when viewing body stimuli and hypothesized altered HR reactions toward those highly significant and emotional stimuli in anorexia nervosa. In total, 37 anorexia nervosa patients and 43 control participants viewed pictures of women of five different weight categories, while their cardiac activity was recorded. R-R intervals following picture onset were determined, and m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 36 publications
0
3
0
Order By: Relevance
“…AN patients also showed no HR differences from Healthy Controls (HC) viewing body-related stimuli (Lutz et al, 2019). AN patients had higher HR changes compared to HC, with a pronounced deceleration after viewing extreme-weight images (Horndasch et al, 2023). More research is needed to clarify the relationship between visual stimuli and HR in AN.…”
Section: Skin Temperaturementioning
confidence: 95%
“…AN patients also showed no HR differences from Healthy Controls (HC) viewing body-related stimuli (Lutz et al, 2019). AN patients had higher HR changes compared to HC, with a pronounced deceleration after viewing extreme-weight images (Horndasch et al, 2023). More research is needed to clarify the relationship between visual stimuli and HR in AN.…”
Section: Skin Temperaturementioning
confidence: 95%
“…Patients with AN exhibit difficulty in emotion processing and regulation, particularly in response to disorder-related stimuli (e.g., food and body-related stimuli) [22][23][24]. Exposure to such stimuli elicits heightened emotional responses in individuals with AN, indicating significant alterations in their emotion processing systems [22][23][24].…”
Section: Emotion Processing and Regulationmentioning
confidence: 99%
“…Patients with AN exhibit difficulty in emotion processing and regulation, particularly in response to disorder-related stimuli (e.g., food and body-related stimuli) [22][23][24]. Exposure to such stimuli elicits heightened emotional responses in individuals with AN, indicating significant alterations in their emotion processing systems [22][23][24]. Research has shown increased activity in the right amygdala of patients with AN-R compared to Healthy Controls (HCs) when exposed to food pictures [25], as well as enhanced amygdala activity in response to body and shape stimuli [26,27].…”
Section: Emotion Processing and Regulationmentioning
confidence: 99%